Trophic structure of fish assemblages in two offshore islands (Ulleungdo and Dokdo) of Korea revealed using stable isotope analysis - Park, Tae Hee; Lee, Dong-Young; Kang, Hee Yoon; Park, Joo Myun; Kim, Dongyoung; Park, Hyun Je (Frontiers in Marine Science, 2024)
The objective of this study was to characterize the trophic structure of fish assemblages on the coasts of offshore islands and the eastern mainland of the Korean Peninsula. We compared the seasonal variability in the trophic structure of fish assemblages between the coasts of two island sites (Ulleungdo and Dokdo) and one mainland site (Hupo), which are on a similar latitude. We analyzed the stable carbon and nitrogen isotope ratios (δ 13 C and δ 15 N) of fish assemblages during spring (April) and summer (August) 2021. No temporal differences in the isotope values of fish and basal resources (i.e., suspended particulate organic matter (SPOM)) were found over the sampling period at the Hupo site. In contrast, at the Ulleungdo and Dokdo sites, the fishes and SPOM showed seasonal differences in the δ 13 C and δ 15 N values between the two seasons. In particular, the fish δ 15 N values at the island sites were relatively higher in summer compared to those in spring, suggesting the seasonal variation in the food chains and/or trophic status between consumers and their dietary sources. These regional isotopic variations also result in differences in the seasonal tendencies of the isotopic niche parameters of fish assemblages between the mainland and island coasts. Such differences in the seasonal isotopic patterns of fish assemblages suggest a relatively substantial shift in the dietary resources available to fish consumers on island coasts compared to those on the mainland coast. Overall, our results suggest that fish assemblages in offshore island coasts have distinct seasonal variability in trophic characteristics in response to changing environmental conditions, including basal resources, compared with fish food webs on the mainland coast at similar latitudes.